Analysis of the Effect of Market and Proactive Orientation with Market Capabilities on Export Performance in East Java Export-Oriented MSMEs - Alicia, Alicia; Wibowo, Januar; Candraningrat, Candraningrat; Supriyanto, Antok (Jurnal Manajemen Bisnis, 2023)
Research aims: This study examines the causal relationships affecting export performance, including market orientation, proactive orientation, and market capability. Design/Methodology/Approach: This study used a quantitative approach, which was carried out by distributing questionnaires to 140 MSMEs in East Java that had already exported. This study was tested utilizing SmartPLS 4 with partial least squares-structural equation model (PLS-SEM) analysis.Research findings: The results exhibited that market orientation significantly affected export performance and market capability. Proactive orientation substantially affected export performance and market capabilities. Besides, market capability directly and significantly influenced the relationship between market orientation, proactive orientation, and export performance.Theoretical Contribution/Originality: Adding market capability as a mediating variable to test the influence of market orientation and proactive orientation on export performance in export MSMEs in Surabaya.Practitioners/Policy Implications: In improving the export performance of MSMEs, oversight institutions or policymakers are expected to provide regular education, training, and guidance on how to observe and take advantage of changes in the export market, obtain information about customers and the export market situation and study and identify opportunities that exist in the export market.Research Limitations/Implications: In this study, the research locations were limited to the Surabaya area, so further researchers can expand the research locations. Data collection can also be done by interviewing, so that respondents are more open to answering questions. In addition, there were only three variables affecting export performance in this study: market orientation, proactive orientation, and market capability. Because the R-Square value of market capability was still at 0.392, or 40%, other independent variables can influence as much as 60%, such as customer orientation, international orientation, demographic orientation, strategic orientation, and others. Besides, the R-Square value of export performance was 0.538, or 54%, so other mediating variables may affect as much as 467%, such as innovation, production, and productive and dynamic capabilities.